Fractures in Children with Spina Bifida - Ahmet Hamdi Akgülle; Feyza Nur Yücel; Evrim Karadağ Saygı (Galenos Yayinevi, 2020)
Objective:The aim of this study is to investigate the frequency of fractures and related factors in children with spina bifida who were followed up in our hospital.Materials and Methods:By retrospectively examination of the medical records of 450 patients with spina bifida, who were followed up by our clinic between 2000 and 2018, the patients were evaluated in terms of factors such as frequency of fracture, age of the first fracture, lesion level, ambulation capacity, physical therapy initiation age, fracture site and mechanism.Results:In the 450 patients examined, the fracture rate was 5.7%. While there was a relationship between low ambulatory capacity and high-level lesions and fracture risk, the early initiation of physical therapy did not protect against fracture.Conclusion:According to these data, fractures are more common in patients with spina bifida. It was concluded that the quality of mobilisation, not the duration, was the more important risk factor for fracture.